1998
DOI: 10.1111/j.0435-3676.1998.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatial patterns of overbank sedimentation on embanked floodplains

Abstract: Middelkoop, H. and Van der Perk, M., 1998: Modelling spatial patterns of overbank sedimentation on embanked floodplains. Geogr. Ann. , 80 A (2): 95-109.ABSTRACT. This paper presents a GIS-based mathematical model for the simulation of floodplain sedimentation. The model comprises two components: (1) the existing hydrodynamic WAQUA model that calculates two-dimensional water flow patterns; and (2) the SEDIFLUX model that calculates deposition of sediment based on a simple mass balance concept with a limited num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 20 publications
8
55
1
Order By: Relevance
“…Floodplain deposition can lead to considerable trapping of sediment and POM amounting to 10-40 % of the annual load (e.g., Walling et al, 2003). Current estimates are based on measured conveyance losses (e.g., Lambert and Walling, 1987), deposition measured during post-event surveys (e.g., Middelkoop and Asselman, 1998;Steiger et al, 2003), and modeling studies (Hung, 2011;Middelkoop and Van der Perk, 1998;Nicholas and Walling, 1997). Sediment trapping efficiencies in floodplains depend on -apart from sediment settling rates -water discharge over the floodplain, the inundated floodplain area and depth, and residence time of the flood water.…”
Section: Floodplain Sediment and Poc Depositionmentioning
confidence: 99%
“…Floodplain deposition can lead to considerable trapping of sediment and POM amounting to 10-40 % of the annual load (e.g., Walling et al, 2003). Current estimates are based on measured conveyance losses (e.g., Lambert and Walling, 1987), deposition measured during post-event surveys (e.g., Middelkoop and Asselman, 1998;Steiger et al, 2003), and modeling studies (Hung, 2011;Middelkoop and Van der Perk, 1998;Nicholas and Walling, 1997). Sediment trapping efficiencies in floodplains depend on -apart from sediment settling rates -water discharge over the floodplain, the inundated floodplain area and depth, and residence time of the flood water.…”
Section: Floodplain Sediment and Poc Depositionmentioning
confidence: 99%
“…Previous studies have indicated that sediment deposition in wetlands is controlled by various factors including the flooding frequency, depth, and duration (French and Spencer 1993;Middelkoop and van der Perk 1998;Reed et al 1999;Temmerman et al 2003;Thonon et al 2007;Schuerch et al 2013), the surface area of the wetland, the suspended sediment load (French and Spencer 1993;Asselman and Middelkoop 1998;Morse et al 2004;Noe et al 2016), and the ability of sediment to settle, which in turn, depends on sediment flow paths (French and Spencer 1993;Siobhan Fennessy et al 1994;Reed et al 1999;Davidson-Arnott et al 2002;Temmerman et al 2003;Anderson and Mitsch 2007;Mitsch et al 2014), wind (Orson et al 1990;Delgado et al 2013), and vegetation (Darke and Megonigal 2003;Temmerman et al 2005;Schile et al 2014;Mitsch et al 2014). These studies were mainly conducted in salt marshes or river flood plains; only few field-based studies were undertaken in freshwater tidal wetlands that represent the transition between these environments.…”
Section: Introductionmentioning
confidence: 99%
“…By coupling hydraulic and sediment deposition models, field-based sedimentation rates and digital elevation models of the floodplain surface were incorporated to numerical modelling in order to reflect the high spatial heterogeneity observed in field-based investigations. Some of these models are based on a discrete-element approach (Stewart et al, 1998;Buttner et al, 2006), and other models on a finite-element approach (Nicholas and Walling, 1997;Nicholas and Walling, 1998;Middelkoop and Van der Perk, 1998). Those techniques advanced the potential to predict sedimentation effects by simple, computationally efficient functions parameterised by distance from the main channel and floodplain elevation.…”
Section: Introductionmentioning
confidence: 99%